2017
DOI: 10.1093/esr/jcx080
|View full text |Cite
|
Sign up to set email alerts
|

Is it Easier to Be Unemployed When the Experience Is More Widely Shared? Effects of Unemployment on Self-rated Health in 25 European Countries with Diverging Macroeconomic Conditions

Abstract: The economic crisis in Europe since 2008 has led to high unemployment levels in several countries. Previous research suggests that becoming unemployed is a health risk, but is job loss and unemployment easier to cope with when unemployment is widespread? Using EU-SILC panel data (2010)(2011)(2012)(2013), this study examines short-term effects of unemployment on self-rated health (SRH) in 25 European countries with diverging macroeconomic conditions. Ordinary least squares regressions show that the unemployed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 33 publications
2
25
0
2
Order By: Relevance
“…In such a situation, the employed-unemployed health inequalities are quite noticeable. 34 Yet, this changes when the economic conditions deteriorate. Now, productive and high-skill individualswith good health status and perhaps better health behavioursbecome unemployed as well due to downsizing and firm closures.…”
Section: Socioeconomic Indicators and Health-related Social Mobilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In such a situation, the employed-unemployed health inequalities are quite noticeable. 34 Yet, this changes when the economic conditions deteriorate. Now, productive and high-skill individualswith good health status and perhaps better health behavioursbecome unemployed as well due to downsizing and firm closures.…”
Section: Socioeconomic Indicators and Health-related Social Mobilitymentioning
confidence: 99%
“…79 Recall that employment status is an elastic socioeconomic indicator sensitive to compositional changes. 34,74,79 Recent empirical evidence has shown that the unemployed population is healthier on average in countries where unemployment becomes a mass phenomenon (e.g. Spain and Greece) 39 .…”
Section: Socioeconomic Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…We estimate the association between current union status and mid-life health using OLS regression methods, which are standard in studies of self-rated health (e.g., Borgonovi and Pokropek 2016 ; Heggebø and Elstad 2017 , n.d.; Williams et al 2011 ). We found nearly identical results using ordered logit models (available on request), but present OLS estimates because they provide the easiest comparison across countries, and categorical or logit models would require arbitrary cut-off points.…”
Section: Methodsmentioning
confidence: 99%
“…In these countries, the experience of being unemployed is widely shared and probably involves less stigma and self-blame. Heggebø and Elstad (2017) demonstrate how non-standard statistical methods may be needed to uncover complex empirical patterns. However, as we shall see, new research designs will also be necessary if the goal is to make more definitive claims about causality in Scandinavian police research.…”
Section: Limited Possibilities For Making Causal Claimsmentioning
confidence: 99%